SOCIAL STUDY ON THE IMPLEMENTATION OF QURAN VALUES IN MANAGING SOCIAL CONFLICT - Novita Syafitri (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2022)
Abstract This study investigates the practical implementation of Quranic values justice (al-‘adl), consultation (shura), peace (salam), and tolerance (tasamuh) in managing social conflicts within Muslim communities in Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis from communities that have experienced social conflict. The findings reveal that the integration of these Quranic values forms a holistic and effective framework for conflict resolution. Communities that applied these values achieved faster and more sustainable conflict resolution, with justice and peace fostering fairness and harmony, while consultation and tolerance promoted inclusivity and social cohesion. This research provides empirical evidence supporting the use of Quranic values in conflict management and offers practical recommendations for community leaders, policymakers, and academics. Additionally, it highlights the potential global relevance of these principles in promoting social harmony in diverse and pluralistic societies.